2020
DOI: 10.1016/j.ymthe.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The SINE Compound KPT-350 Blocks Dystrophic Pathologies in DMD Zebrafish and Mice

Abstract: Duchenne muscular dystrophy (DMD) is an X-linked muscle wasting disease that is caused by the loss of functional dystrophin protein in cardiac and skeletal muscles. DMD patient muscles become weakened, leading to eventual myofiber breakdown and replacement with fibrotic and adipose tissues. Inflammation drives the pathogenic processes through releasing inflammatory cytokines and other factors that promote skeletal muscle degeneration and contributing to the loss of motor function. Selective inhibitors of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 86 publications
4
18
0
Order By: Relevance
“…Although we did not observe positive results with the serotonin modulators, we did observe significant efficacy with 2.5 μg/ml aminophylline, a non-specific PDE inhibitor, in both the short-and long-term zebrafish assays. This is consistent with and reaffirms the results of Kawahara et al (2011), who first identified aminophylline to ameliorate the dystrophic phenotype of sapje zebrafish, as well as the results of subsequent investigators (Hightower et al, 2020;Waugh et al, 2014). Despite variable clinical trial success with PDE5 inhibitors such as sildenafil and tadalafil and side effects associated with other non-specific PDE inhibitors such as pentoxiphylline (Spinazzola and Kunkel, 2016), our results suggest that PDEs may still be a relevant target for DMD therapeutics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although we did not observe positive results with the serotonin modulators, we did observe significant efficacy with 2.5 μg/ml aminophylline, a non-specific PDE inhibitor, in both the short-and long-term zebrafish assays. This is consistent with and reaffirms the results of Kawahara et al (2011), who first identified aminophylline to ameliorate the dystrophic phenotype of sapje zebrafish, as well as the results of subsequent investigators (Hightower et al, 2020;Waugh et al, 2014). Despite variable clinical trial success with PDE5 inhibitors such as sildenafil and tadalafil and side effects associated with other non-specific PDE inhibitors such as pentoxiphylline (Spinazzola and Kunkel, 2016), our results suggest that PDEs may still be a relevant target for DMD therapeutics.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, we used this value as a basis for our DMSO and untreated control groups, and assessed whether each drug significantly decreased this percentage. We used the non-selective phosphodiesterase (PDE) inhibitor aminophylline as our positive control, which was discovered as a positive effector in a previous zebrafish drug screen in our lab and also confirmed independently (Hightower et al, 2020;Kawahara et al, 2011;Waugh et al, 2014). Aminophylline (2.5 μg/ml) consistently decreased the percentage of affected fish to 10-15% in our experiments.…”
Section: Short-term Drug Screening In Sapje and Sapje-like Zebrafish supporting
confidence: 71%
“…These large-scale screens, which applied either pools of eight chemicals or individual chemicals to dmd mutant zebrafish, have tested over 4000 compounds and identified 25 positive hits [ 43 ]. In addition, some small molecules, such as TSA, have been shown to ameliorate both dmd mutant zebrafish and mdx mice [ 27 , 45 , 50 52 ]. Because of this strong conservation, insight from zebrafish can inform our understanding of human DMD disease, while also taking advantage of the utility of high-throughput analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish eggs can be rapidly produced in large numbers, the resulting embryos readily absorb drug compounds, and muscle development and structure can easily be observed in vivo through birefringence techniques (Berger et al, 2012; Granato et al, 1996; Kawahara et al, 2011). Because the zebrafish dmd mutation, in contrast to the mdx mouse and DMD mdx rat, is lethal during juvenile stages, survival can be used as an outcome measure for drug treatments (Hightower et al, 2020; Kawahara et al, 2011; Kawahara et al, 2014). Large-scale drug screens have highlighted the potential of dmd zebrafish for identifying new therapeutic compounds and targets as well as for understanding the molecular mechanisms behind DMD (Kawahara et al, 2011; Kawahara et al, 2014; Waugh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale drug screens have highlighted the potential of dmd zebrafish for identifying new therapeutic compounds and targets as well as for understanding the molecular mechanisms behind DMD (Kawahara et al, 2011; Kawahara et al, 2014; Waugh et al, 2014). In addition, dmd zebrafish can replicate drug effects seen in mdx mice (Hightower et al, 2020; Johnson et al, 2013; Kawahara et al, 2011; Li et al, 2014; Winder et al, 2011). Because of this strong conservation, insight from zebrafish can inform mammalian DMD studies, while also taking advantage of the utility of high-throughput analysis.…”
Section: Introductionmentioning
confidence: 99%